Apprenticeship training in Spain - a cost-effective model for firms? : a cost-benefit simulation study - Wolter, Stefan C. [Verfasser]; Mühlemann, Samuel [Verfasser] (Bertelsmann Stiftung, 2015)
"Apprenticeship training is a form of vocational education characteristic of German-speaking countries. The most salient feature of this form of vocational education is the combination of school-based instruction with work-based learning. This combination of in-class and in-firm learning is often credited as an antidote against youth unemployment: receiving training from a company allows apprentices to gather working experience, which in turns makes their transition into the labor market more efficient. In recent years, therefore, the persistence of high youth unemployment rates in many industrialized countries has brought the apprenticeship training model to the attention of policymakers and business leaders. In order to introduce an apprenticeship training model, governments must convince firms to engage in vocational training by providing on-the-job training for apprentices. Since the outbreak of the last economic crisis in 2007-2008, the apprenticeship training model has also caught the attention of Spanish political leaders concerned with the country's high rates of youth unemployment. The first pilot projects took place in 2011, and in 2012, apprenticeship training became part of Spain's vocational education system. However, the involvement of Spanish firms has remained rather low, which is probably due to firms' inability to obtain net benefits off apprenticeship training under the current training system. This study therefore seeks to determine under which circumstances Spanish firms could benefit from participating in apprenticeship training, that is, whether the introduction of modifications in Spain's current model could result in net benefits for Spanish firms. More specifically, this study tries to answer the question whether an average Spanish firm, in Spain's current economic environment, could expect a net benefit from implementing an apprenticeship training model similar to the one employed by Swiss firms." (Editor, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 3.2 Unternehmen und Behörden; S 4 Kosten & Finanzierung; I 2.2.1 Westeuropa; Berufsausbildung; Unternehmen; Ausbildungskosten; Kosten-Nutzen-Relation; Spanien